Single M-Line Is as Reliable as Multiple M-Line Ultrasound for Carotid Artery Screening - Malik, Afrah E. F.; Delhaas, Tammo; Spronck, Bart; Henry, Ronald M. A.; Joseph, Jayaraj; Stehouwer, Coen D. A.; Mess, Werner H.; Reesink, Koen D. (Frontiers in Physiology, 2021)
Purpose: Carotid artery properties can be evaluated with high accuracy and reproducibility using multiple M-line ultrasound. However, the cost of multiple M-line based imaging modalities and the extensive operator expertise requirements hamper the large-scale application of arterial properties assessment, particularly in resource-constrained settings. This study aims to assess the performance of a single M-line approach as an affordable and easy to use alternative to multiple M-line imaging for screening purposes. Methods: We used triplicate longitudinal common carotid artery ultrasound recordings (17 M-lines covering about 16 mm, at 500 frames per second) from 500 subjects from The Maastricht Study to assess the validity and reproducibility of a single against multiple M-line approach. The multiple M-line measures were obtained by averaging over all available 17 lines, whereas the middle M-line was used as proxy for the single M-line approach. Results: Diameter, intima-media thickness (IMT), and young’s elastic modulus (YEM) were not significantly different for the single and multiple M-line approaches (p>0.07). Distension and distensibility coefficient (DC) did differ statistically significantly (p<0.001), however technically irrelevant. Similarly, Bland-Altman analysis revealed good agreement between the two approaches., The single M-line approach, compared to multiple M-line, exhibited an acceptable reproducibility coefficient of variation for diameter (2.5% vs. 2.2%), IMT (11.9% vs. 7.9%), distension (10% vs. 9.4%), DC (10.9% vs. 10.2%) and YEM (26.5% vs. 20.5%). Furthermore, both methods showed a similar capability to detect age-related differences in arterial stiffness in our study population. Conclusion: Single M-line ultrasound appears to be a promising tool to estimate anatomical and functional common carotid artery properties with very acceptable validity and reproducibility. Based on our results we might infer that image-free, single M-line tools could be suited for screening and population studies in low-resource settings worldwide.